The optimal organization structure design problem in make-to-order enterprises - Mena, Jesus Alonso; Chen, Chin-Sheng (International Journal of Industrial Engineering: Theory, Applications and Practice, 2012)
This paper addresses the organization structure design problem in a make-to-order (MTO) operation environment. A mathematical model is presented to aid an operations manager in an MTO environment to select a set of potential managerial layers to minimize the operation and supervision cost. With a given Work Breakdown Structure (WBS) for any specific project, solving this model leads an optimal organization structure design. The proposed model considers allocation tasks to workers, considering complexity and compatibility of each task with respect to workers, and the requirement of management for planning, execution, training and control in a hierarchical organization. This model addresses the span of control problem and provides a quantitative approach to the organization design problem and is intended for applications as a design tool in the make-to-order industries.